Library as «the third place»: realization of the concept - M. F. Kryazheva; E. S. Shakirova (Библиосфера, 2019)
The concept of «third place», formulated by R. Oldenburg, can be used as one of the tools for a library transformation. «The third place» is a multifunctional public space, that provides opportunities for intellectual and cultural communication, creativity, self-development and self-expression, a place where one wants to be and wants to return («the first place» according to this concept is home, «the second place» – work or study). The purpose of this article is to consider the concept of «the third place» in the context of its realization in the library and information sphere in Tumen (Russia). Various relevant documents regulating the work of libraries (first of all – public libraries) contain positions confirming the interrelation of library and information activity with the concept of «the third place». Many characteristics of «the third places» («humanitarian», technical and technological, etc.) determine the direction of work of libraries at the modern stage. For the study several similar characteristics were chosen: accessibility, locality; openness to all social categories; the possibility for leisure, entertainment; comfort, ease of interaction. The method of survey with elements of the semantic differential was used. The respondents were the users of the Information and library center for youth (Tyumen, Russia). The research was to identify the degree of severity of these characteristics in library.The results of survey analysis allow the confirmation that the activity of the Information and library center for youth corresponds to the characteristics of «the third place». Librarians work on their integration and development constantly. Also they preserve the major, document-information, content of activity of libraries.The concept of «the third place» is not the only option for the development of each library, but it provides the possibility of using a certain set of conceptual characteristics as a working tool for library and information activity.